DIFFERENCES IN SLEEP QUALITY AMONG NURSING STUDENTS - Nisa, Khairun; Mulyadi, Mulyadi (Nursing Current: Jurnal Keperawatan, 2023)
The sleep quality and academic performance of students are influenced by their activity patterns, which in turn affects their health status. Nevertheless, there is a scarcity of research specifically addressing sleep problems among nursing students. The objective of this study is to identify and analyse the features of nursing students that are associated with variations in their sleep quality. This study employs a correlational descriptive research design, utilising a quantitative technique. A total of 117 individuals were surveyed. The Mann-Whitney and Kruskal-Wallis tests were employed to assess variations in sleep quality according to the attributes of the participants. The findings indicated that a significant majority of participants, up to 87.2%, experienced substandard sleep quality. Based on the subjective evaluation of PSQI components, 50.4% of participants were classified as having good sleep quality. Additionally, 34.2% reported experiencing difficulty falling asleep more than three times a week within 30 minutes. The majority of participants (42.5%) reported a sleep duration of 6-7 hours. Furthermore, 4.3% of participants had taken sleeping pills in the past month. Furthermore, the results demonstrated a strong correlation between the ages of the respondents and their sleep quality (p=0.047). This study uncovers a worrisome pattern indicating that the sleep quality of nursing students is significantly subpar. Hence, it is imperative to employ both academic and non-academic strategies and advancements to enhance the quality of students' sleep.